NES and NNES Teachers: A Cross-cultural Comparison of Teaching Styles (American & British Studies Annual, 2008)
The paper investigates the differences and similarities in teaching styles from a cross-cultural perspective. Although the dichotomy between native and non-native English speaking teachers has been the focus of numerous publications in the field, various elements of their teaching styles, in terms of both similarities and differences, have received little attention. For this purpose, authors surveyed teachers in the U.S. and the Czech Republic to analyze their general modes of classroom behavior, teaching methods, and self-image. Empirical evidence received through the survey does not fully support the idea that cultural factors influence certain aspects of classroom practices and teaching style.
Keywords: teaching styles; native English speaking teachers; non-native English speaking teachers; cross-cultural; classroom behavior; teacher´s self-image